The Influence of Applying Educational Active Drama in enhancing speaking skills in Teaching- learning English Language: A Theoretical Perspective - Tahani R. K. Bsharat,; Barahmeh, Mosaddaq (Technium Social Sciences Journal, 2020)
Speaking skills play a crucial role in this modern world, and one must develop these skills in order to excel in teaching-learning processes. Speaking is therefore the most important ability of all the four language skills to communicate effectively in this global environment. Since English is commonly used throughout the world, learners need to acquire their communication skills to be effective in their respective fields. The classroom is thus the ideal platform for the acquisition of good communication skills, especially speaking skills. The teachers have to consider and seek to incorporate different teaching methods in their classrooms in order to improve the language skills of their learners in English classrooms such as educational drama with active learning. thus, teachers can do this by modifying their methods and materials and using the latest teaching skills techniques. The teachers should, therefore, incorporate some community and pair exercises in their daily English classrooms which can significantly improve their speaking skills. This paper sheds light on the importance of applying educational active Drama in enhancing speaking skills in Teaching-learning English Language. First of all, this paper discloses the significance of speaking skills. Later, this paper also explains the importance of an active learning system. It also explains the educational drama and its techniques in teaching-learning the English language especially speaking skills. Finally, this paper suggests a new teaching-learning method which is educational active drama in enhancing speaking skills.